Hardware IP Security and Trust - Mishra, Prabhat; Bhunia, Swarup; Tehranipoor, Mark (Springer International Publishing : Imprint: Springer, 2017)
This book provides an overview of current Intellectual Property (IP) based System-on-Chip (SoC) design methodology and highlights how security of IP can be compromised at various stages in the overall SoC design-fabrication-deployment cycle. Readers will gain a comprehensive understanding of the security vulnerabilities of different types of IPs. This book would enable readers to overcome these vulnerabilities through an efficient combination of proactive countermeasures and design-for-security solutions, as well as a wide variety of IP security and trust assessment and validation techniques. This book serves as a single-source of reference for system designers and practitioners for designing secure, reliable and trustworthy SoCs.